(untitled) - Dees, J. Gregory (New York, 2001)
The rising spirit of social entrepreneurship has created all kinds of new opportunities for nonprofit organizations. But at the same time, many are discovering more than their share of challenges as well. This essential book will help anyone in the field gain the necessary skills to meet these challenges. Written by the leading thinkers and practitioners in the field, Enterprising Nonprofits offers concise and engaging explanations of the most successful business tools being used by nonprofits today. The authors clearly describe all the concepts so you'll be able to embrace the methods of social enterprise for your organization. With this book, you'll learn how to use practical business techniques to dramatically improve the performance of your nonprofit.
Keywords: Hành động trên mạng xã hội,Tổ chức phi lợi nhuận,Nonprofit organizations,Social action; Quản trị